A Colorimetric Chemosensor Based on a Nozoe Azulene That Detects Fluoride in Aqueous/Alcoholic Media - Murfin, Lloyd C.; Chiang, Kirstie; Williams, George T.; Lyall, Catherine L.; Jenkins, A. Toby A.; Wenk, Jannis; James, Tony D.; Lewis, Simon E. (Frontiers in Chemistry, 2020)
Colorimetry is an advantageous method for detecting fluoride in drinking water in a resource-limited context, e.g. in parts of the developing world where excess fluoride intake leads to harmful health effects. Here we report a selective colorimetric chemosensor for fluoride that employs an azulene as the reporter motif and a pinacolborane as the receptor motif. The chemosensor, NAz-6-Bpin, is prepared using the Nozoe azulene synthesis, which allows for its rapid and low-cost synthesis. The chemosensor gives a visually observable response to fluoride both in pure organic solvent and also in water/alcohol binary solvent mixtures.